Durum wheat improvement against fungal pathogens by using protein inhibitors of cell wall degrading enzymes - D'Ovidio R.; Moscetti I.; Janni M.; Volpi C.; Kalunke M.R.; Tundo S.; Sella L.; Favaron F. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
We report the use of three glycosidase inhibitors, the bean polygalacturonase inhibiting protein 2 (PvPGIP2), the kiwi pectin methyl esterase inhibitor (AcPMEI), and the Triticum aestivum xylanase inhibitor III (TAXI-III), to control leaf blotch and Fusarium Head Blight (FHB) symptoms caused by the fungal pathogens Bipolaris sorokiniana and Fusarium graminearum. We produced transgenic durum wheat lines by particle bombardment using these inhibitors singly or in combination. We pyramided these transgenes also by classical crossing of transgenic lines carrying a single transgene. Phyto-pathological tests performed in controlled conditions showed that the expression of these inhibitors has the potential to engineer a broad-spectrum disease resistance in wheat.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)